IBN KHALDUN’S CONCEPT OF ʿASABIYYAH: SOCIAL COHESION, POLITICAL CYCLES, AND THE FOUNDATIONS OF CIVILIZATION - Nazirov Sherzodbek Rustamsher o’g’li (Bright Mind Publishing, 2025)
This article explores the life, intellectual legacy, and social philosophy of Ibn Khaldun (1332–1406), a prominent Arab-Muslim thinker considered a forerunner of sociology and the philosophy of history. Particular attention is given to his seminal concept of ʿasabiyyah (social solidarity), which he employed to explain the rise and decline of civilizations. Drawing on Ibn Khaldun’s Muqaddimah, the study highlights the dual function of ʿasabiyyah: its positive role in fostering cooperation, cohesion, and state formation, as well as its limitations when compared to the Islamic notion of brotherhood. The article reviews both classical and contemporary scholarship—from Rosenthal’s philological analysis to modern sociological reinterpretations—demonstrating that Ibn Khaldun’s theory remains relevant for analyzing political cycles, demographic change, and social dynamics across civilizations. The discussion concludes that ʿasabiyyah serves as a universal principle of collective action and historical transformation, with enduring significance for modern social sciences.
Keywords: Ibn Khaldun, Muqaddimah, Asabiyyah, social philosophy, social cohesion, political cycles, Islamic thought, sociology of history, civilization, group solidarity.